A randomized controlled trial: the efficacy of eluoride rinse combined with calcium pre-rinse to increase overnight salivary fluoride. (October 2013) - Chen, Margaret Sällberg; Strömberg, Elin; Vogel, Gerald Lee; Sandborgh-Englund, Gunilla
Abstract Background. Previous studies have shown that a calcium (Ca) pre-rinse given before a 228 ppm fluoride (F) rinse greatly increased salivary fluoride. Objectives. The aim of this randomized controlled trial is to examine if Ca pre-rinse could increase the fluoride concentration in the overnight unstimulated saliva after a 905 ppm F-rinse. Materials and methods. Pre-rinses containing 150 mM, 75 mM or 0 mM Ca-lactate prepared by a validated pharmaceutical cGPM procedure were tested by nine subjects in a randomized order immediately followed by a 905 ppm F-rinse. The fluoride concentration was measured in unstimulated saliva collected 10 h later. Results and conclusions. The Ca pre-treatment significantly increased F level in overnight saliva following the 905 ppm fluoride rinse by 1.7× relative to the 905 ppm F-rinse alone; however, a significant effect was only observed with the highest (150 mM) Ca concentration as pre-rinse. Clinical relevance. High concentration F rinses (905 ppm) are commonly recommended for patients at high-risk of caries. A pre-treatment with high levels of Ca may further improve the cariostatic effect of this ion.